Delayed Urethral Obstruction after Migration of a Ballistic Pellet in an Alpine Wether - Joe S. Smith; Adrien-Maxence Hespel; Jessica D. Garcia; Krista L. Lipe; Stephanie A. Kleine; Pierre-Yves Mulon (Case Reports in Veterinary Medicine)
A one-year-old alpine wether was presented for emergency evaluation of stranguria. Diagnostics identified a moderately distended bladder and mild dehydration. Preliminary lateral radiographs identified two metallic structures consistent with projectile pellets in the pelvic and perineal regions and no evidence of radiopaque uroliths. A tube cystostomy was performed, and a contrast urethrogram revealed one of the pellets in the perineal region was in proximity to the urethral obstruction. Subsequent radiography and ultrasound identified the pellet as being within the lumen of the urethra. Examination of the trichotomized skin revealed two scars, including a scar over the paralumbar fossa in the region of the urinary bladder suggestive of a projectile injury. The pellet was removed by a perineal urethrotomy. The patient was able to spontaneously urinate after urethrotomy, passed a tube cystostomy challenge two weeks after surgery, and was discharged. No complications were reported. While uncommon in the veterinary and comparative medical literature, clinicians should consider the potential for projectile pellets to migrate into the urinary tract after initial injury.